1992
DOI: 10.1149/1.2069389
|View full text |Cite
|
Sign up to set email alerts
|

H Insertion and Electrochromism in NiO x Thin Films

Abstract: NonstoichiometriC, anhydrous NiO~ thin films were produced by sputtering. They can be bleached by means of hydrogen insertion equally fast and efficiently either in an electrochemical cell or in a gas chamber, as demonstrated in this work by using a Pd covered thin film electrode. The electrode mechanical stress and transmittance changes during H insertion and extraction, measured in situ, showed an increase in the compressive stress in the cathodic (bleaching) cycle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…This top layer serves as a membrane that only allows H + to penetrate to the underlying film. 403 Thus all other ions-such as OH 2 and K + -were filtered out. It should be noted, for completeness, that the Pd layer did not display any optical modulation in the pertinent voltage range.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…This top layer serves as a membrane that only allows H + to penetrate to the underlying film. 403 Thus all other ions-such as OH 2 and K + -were filtered out. It should be noted, for completeness, that the Pd layer did not display any optical modulation in the pertinent voltage range.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Although flexible display technologies have been well developed, challenges such as reducing fabrication costs, operating at low temperatures, simplifying device structures, and operating at a low voltage remain. Electrochromic (EC) film [1][2][3][4][5][6][7][8][9][10][11][12][13] has attracted considerable attention because of low temperature fabrication, low power operation, and energy-saving design, which have contributed to potential applications in green building (smart windows), electric vehicle (auto-dimming glass), and wearable electronics (flexible displays). Among the various materials used in EC films, electroplated tungsten oxide (WO 3 ) [6][7][8][9][10][11][12][13] has demonstrated high potential because of its low cost, high optical contrast, and stability.…”
Section: Introductionmentioning
confidence: 99%
“…21 However, as an electrochromic material, NiO shows best performance with alkaline electrolytes that support OH − intercalation. 22 Later, we used PB-modified ITO substrate as a counter electrode, which is a fast switching electrochromic material operating via K + ion intercalation. The switching speed of the PB-based devices dramatically increased compared to that of the NiObased windows, but we found that PB is not compatible with Bi−Cu electrolytes and that Cu 2+ irreversibly reacts with PB.…”
Section: Introductionmentioning
confidence: 99%